Design of efficient QCA multiplexers. (19th May 2015) - Cocorullo, G.; Corsonello, P.; Frustaci, F.; Perri, S.
Summary: A new methodology to realize efficient multiplexers using quantum‐dot cellular automata (QCA) is presented in this paper. The novel designs here demonstrated fully exploit the intrinsic logic capabilities of the basic building block in the QCA domain: the Majority Gate. An efficient logic formulation is derived for the 4:1 multiplexing function that can be recursively applied to the realization of multiplexers with any fan‐in, by adding in the worst‐case path only one level of Majority Gate for each input doubling. A 16:1 multiplexer designed by applying the proposed recursive approach requires less than 1600 cells and consumes only 12 clock phases to complete the operation. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : We present a new methodology to realize efficient large fan‐in multiplexers using quantum‐dot cellular automata (QCA). It is based on innovative formulations leading to recursive structures able to achieve increased speed performances and reduced overall sizes with respect to the existing competitors. Thanks to the logic and layout strategies adopted, a fully recursive 16:1 MUX designed as described in this paper exhibits a delay of only three clock cycles and occupies an active area of 1.45 µm 2 with a density of 1097 cells per µm 2 . The fastest partially recursive counterpart here designed performs its computation within 3 + 1 4 clock cycles and occupies an overall area of 1.72 µm 2 with a density of 902 cells per µm 2 .